Hyperfine Interactions and Metal Atom Dynamics in a Number of Stannyl Phosphide Compounds and the Detailed Crystal Structure of Triphenyltin Chloride Revisited. Issue 10 (4th March 2016) - Bogoslavsky, Benny; Nowik, Israel; Herber, Rolfe H.
Abstract: Temperature‐dependent 119 Sn Mössbauer effect (ME) spectroscopy has been used to elucidate the hyperfine parameters (isomer shift and quadrupole splitting) as well as the dynamics of the motion of tin in three triphenyltin phosphide complexes, namely P(SnPh3 )3 (C54 H45 PSn3, 1 ), P7 (SnPh3 )3 (C54 H45 P7 Sn3, 2 ), and [Na(benzo‐15‐crown‐5)][P(SnPh3 )2 ] (C50 H50 NaO5 PSn2, 3 ), as well as in triphenyltin chloride (4 ). Although the isomer shifts are very similar for all four compounds, the quadrupole splitting is dependent upon their detailed structures. The metal atom vibrations are essentially isotropic with respect to the principal symmetry axis passing through the tin atom and the triphenyltin moiety. The crystal structure of triphenyltin chloride has been re‐determined at four different temperatures, and the root‐mean‐square amplitudes‐of‐vibration of the metal atom have been evaluated from the crystallographic U i, j values and compared with the corresponding data derived from the Mössbauer measurements. These metal atom dynamics have been compared with those of the stannyl phosphide complexes derived from ME data and related to their structural details. The sensitivity of the ME technique with respect to elucidating the metal atom dynamics is demonstrated in detail. Abstract : The figure shows the 95 K 119 Sn Mössbauer spectrum of P(SnPh3 )3 and P7 (SnPh3 )3, which share a common triphenyltin moiety with triphenyltin chloride. The primary effect of the Sn–P ligation is the near collapse of the quadrupole splitting in the phosphide complexes.